Evolution of ceftazidime-avibactam resistance driven by variation in blaKPC-2 to blaKPC-190 during treatment of ST11-K64 hypervirulent Klebsiella pneumoniae - Liu, Zeshi; Lei, Jing; Zhang, Xue; Yin, Jian; Zhang, Yanping; Lei, Ke; Geng, Yan; Huang, Lingjuan; Han, Qiang; He, Aili (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe emergence of Klebsiella pneumoniae carbapenemase (KPC) variants has significantly compromised the efficacy of ceftazidime-avibactam (CZA), a critical antibiotic for treating carbapenem-resistant K. pneumoniae (CRKP) infections. This study investigates the novel KPC-190 variant, identified in a hypervirulent ST11-K64 K. pneumoniae strain during CZA therapy, which confers resistance to CZA while partially restoring carbapenem susceptibility.MethodsThe K. pneumoniae clinical isolate LX02 harboring blaKPC-190 was characterized using antimicrobial susceptibility testing, whole-genome sequencing (Illumina and Nanopore), and plasmid analysis. Functional studies included plasmid transformation, cloning assays, and enzyme kinetics (spectrophotometric analysis of purified KPC-190 protein). Genetic context was mapped using bioinformatics tools (RAST, ResFinder, Proksee), and virulence determinants were identified.ResultsKPC-190 exhibited a unique resistance profile: high-level CZA resistance (MIC >64 μg/mL) with reduced carbapenem MICs (imipenem MIC = 2 μg/mL). Enzyme kinetics revealed decreased Kcat/Km for carbapenems and ceftazidime, alongside a 9-fold higher IC50 for avibactam (0.13 μM vs. KPC-2’s 0.014 μM). Genomic analysis identified blaKPC-190 within an IS26 flanked mobile element (IS26-ISKpn8-blaKPC-ΔISKpn6-ΔtnpR-IS26) on an IncFII plasmid. The strain also carried hypervirulence markers (rmpA2, iucABCD-iutA, and type 1/3 fimbriae).DiscussionThe KPC-190 variant underscores the adaptive evolution of blaKPC under antibiotic pressure, combining CZA resistance via enhanced ceftazidime affinity and avibactam evasion with retained carbapenem hydrolysis. Its association with hypervirulence plasmids and IS26-mediated mobility poses a dual threat for dissemination. These findings highlight the urgent need for genomic surveillance and alternative therapies (e.g., meropenem-vaborbactam) to address KPC-190-mediated resistance.